The Development of Distributed Systems in Supporting Scalability and Availability of Modern Cloud Computing-Based Digital Services: Perkembangan Sistem Terdistribusi dalam Mendukung Skalabilitas dan Ketersediaan Layanan Digital Modern Berbasis Cloud Computing - Siti Aisyah Empo; Rahmaniar Rahmaniar (Program Studi Teknologi Rekayasa Komputer dan Jaringan, Politeknik Wahdah Islamiyah Makassar, 2026)
This study aims to examine the development of distributed systems in supporting the scalability and availability of modern digital services. The rapid growth of digital services across various sectors requires information systems that can handle increasing workloads while maintaining continuous service availability. Distributed systems have emerged as a key architectural approach to address these demands through workload distribution, efficient resource management, and system resilience. This research employs a qualitative method using a literature review approach. Data were collected from textbooks, indexed national and international journal articles, and scientific conference proceedings related to distributed systems, cloud computing, and microservices architecture. The collected literature was analyzed descriptively and comparatively to identify key concepts, architectural models, and research findings related to scalability and service availability. The results indicate that distributed systems have evolved significantly with the adoption of cloud computing and microservices architecture. These technologies support horizontal scalability, enhance system flexibility, and improve service availability through redundancy and data replication mechanisms. The study concludes that distributed systems play a crucial role as the foundation of modern digital services by enabling scalable, reliable, and sustainable digital infrastructures.